Abiotic stress upregulated TaZFP34 represses the expression of type-B response regulator and SHY2 genes and enhances root to shoot ratio in wheat - Chang, Hongping (Plant science : an international journal of experimental plant biology, 2016)
Copyright © 2016 Elsevier Ireland Ltd. All rights reserved.